Analysis of different populations accessing online overdose response training and harm reduction supplies (ADORES) - Michaela Pacheco; Abiodun Ologunowa; Anita Jacobson (BMC, 2024)
Abstract Background An online mail order naloxone and harm reduction supply program was created by an interdisciplinary team at the University of Rhode Island College of Pharmacy and hosted on the university website (UNIV). The program was subsequently funded by the Rhode Island Department of Health (DOH) and added to the DOH website. This study compares demographic characteristics of the two populations submitting requests through the program's distinct access points, UNIV and DOH, to those of populations at-risk for overdose. Methods This is a retrospective comparative analysis using voluntarily provided information from mail order request forms submitted through two websites from June 2020 through October 2023. The primary objective was to compare demographic characteristics of requesters through the two access points to those of individuals at-risk for experiencing or responding to an overdose. Descriptive statistics were used to characterize the two distinct populations. Chi-square tests were performed to determine if statistically significant differences in population demographics existed between access points. Odds ratios were estimated using a simple logistic regression model to assess the relationship between access point and demographic characteristic to determine if either access point had a greater likelihood of reaching individuals with at-risk demographics. Results A total of 5,783 (UNIV = 1662; DOH = 4121) mail order request forms were included in the analysis. Participants who completed requests through UNIV were more likely to be 44 years old or younger and/or reside in rural areas. Participants who submitted requests through DOH were more likely to reside in non-rural and/or low-income areas, and/or identify as gender minorities. Additionally, UNIV respondents were more likely to be first-time naloxone requesters while DOH respondents were more likely to have obtained and used naloxone before. Conclusions Results establish that different access points can reach different at-risk population subsets and support the use of multiple access points and advertising strategies to expand the reach of online mail order harm reduction programs. Study registration The study was retrospectively approved by the University of Rhode Island Institutional Review Board (IRB reference #2124391-2).